Keterkaitan Pola Asuh Autoritatif dan Harapan Lulus Tepat Waktu terhadap Kegigihan Akademik Mahasiswa Beasiswa - Fella Rohadhatul Aisy; Ridwan Budi Pramono (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
This study examines the correlation between authoritative parenting style parenting and hope to graduate on time to academic grit in students who receive full scholarships. It was conducted on 87 full-scholarship undergraduate students selected through purposive sampling. Research instruments included measures of academic grit, authoritative parenting style, and hope to graduate on time. Findings revealed a strong correlation (p = 0.000; R = 0.771; R2 = 0.595) among authoritative parenting style, hope to graduate on time, and academic grit, contributing effectively by 59.5%. The results of the minor hypothesis indicate a highly significant positive relationship between authoritative parenting style and academic grit (R = 0.576, p < 0.01), along with a highly significant positive correlation between hope to graduate on time and academic grit (R = 0.733, p < 0.01). Based on the research outcomes, it can be concluded that a highly significant positive correlation among the three variables.